Grain yield response to planting date and cutting height of the first crop in rice ratooning - Nakano, Hiroshi; Tanaka, Ryo; Hakata, Makoto (Crop science, 2023)
Rice (Oryza sativa L.) ratooning is one of the most essential production strategies to increase grain yield. Field experiments were conducted in southwestern Japan in 2021 and 2022 to determine the effects of planting date and cutting height of the first crop on grain yield. Grain yield of the second crop was higher at early planting date than at late planting date in 2021, but the yield difference was narrowed in 2022. The higher grain yield at early planting date resulted from the higher number of spikelets and percentage of filled spikelets due to the higher stubble nonstructural carbohydrate (NSC) content, leaf area index (LAI), and air temperatures. Grain yield of the second crop was higher at high cutting height than at low cutting height in 2021, but the yield difference was narrowed in 2022. The higher grain yield at high cutting height resulted from the higher number of spikelets due to the higher NSC content and LAI. In the weather conditions, grain yield had a strong positive correlation with the air temperature, which had positive correlations with the number of panicle and percentage of filled spikelets. In the stubble conditions, grain yield had a strong positive correlation with NSC content, which had positive correlations with the number of panicle and percentage of filled spikelets. Therefore, early planting, which secures high air temperatures, and high cutting height, which produces high NSC content, are recommended to increase grain yield of the second crop. Core Ideas Early planting date generally had higher yield of the second crop. Yield difference of the second crop between planting dates was narrowed under high air temperature condition. High cutting height generally had higher yield of the second crop than low cutting height. Yield difference of the second crop between cutting heights was narrowed under high air temperature condition. Early planting and high cutting height are recommended to increase yield of the second crop.